Analysis of aflatoxin B1 in contaminated feed, media, and serum samples of Cyprinus carpio L. by high-performance liquid chromatography. Issue 4 (31st July 2018) - Jangampalli Adi, Pradeepkiran; Matcha, Bhaskar
Abstract: Objectives: Enzyme-linked immunosorbent assay (ELISA)-, thin-layer chromatography (TLC)-, and highperformance liquid chromatography (HPLC)-sensitive methods were used for the identification of aflatoxin B1 (AFB1) contaminated fish feed, media, and fish serum samples. Materials and Methods: The ELISA, TLC, and HPLC methods were validated by the quantitative and qualitative determination of AFB1 in contaminated fish feed, media, and fish blood serum samples. Results: The primary identification of AFB1 was carried out with a DOA-ELISA test kit ELISA followed by TLC with RF values 0.81, 0.79, 0.81, and 0.80 of AFB1-contaminated fish feed, media, and serum samples, respectively, compared with AFB1 standard. HPLC results show that the AFB1 levels in contaminated fish feed, media, and serum samples were 2.6, 2.6, and 2.7 ng/mL, concentrations respectively. The level of concentrations of AFB1 was almost similar in all three samples, but slightly higher in the fish serum sample with, 2.7 ng/ml. However, the present method is strongly recommended for monitoring AFB1 contamination in feed stuffs, especially in fisheries where the feed is under continuous exposure to moisture. Conclusions: This method is accurate and more sensitive when compared with routine conventional AFB1 detection methods, and is highly applicable in aquaculture and fisheries to screen the mycotoxins in fish feed.